Bipolar Fuzzy Soft Hyperideals and Homomorphism of Gamma-Hypersemigroups - Arulmozhi, K.; Chinnadurai, V.; Seenivasan, M. (International Journal of Engineering and Technology, 2018)
In this paper, we introduce the concept of bipolar fuzzy soft gamma hyperideals in gamma hyper semigroups. We define bipolar fuzzy soft hyper ideals, bi-ideals and interior ideals of gamma hyper semigroups and discuss some properties.Â Â